Investigation of Aboveground Interspecific Interaction in the Intercropping Culture of Soybean (Glycine max (L) Merrill) and Niger (Guizotia abyssinica Cass) - Meisam Namdari; Rahmat Abbasi; Hemmatollah Pirdashti; faezeh zaefarian (بوم شناسی کشاورزی, 2023)
IntroductionToday, increasing sustainability in agriculture is essential to meet future food needs. In this regard, the intercropping culture has been considered as viable and environmentally friendly approach to sustainable agriculture. Further, investigation of complementary species relationships in annual cropping systems could be addressed to achieve sustainability and development. In order to fully understand the inter-specific interactions between crops, it is crucial to know how to react to neighboring species. The selection of species with the different spatial structures in the intercropping culture pattern can be helpful in this regard. The differences of crop’ canopy in intercropping cultivation increase the efficiency of using water, light, and nutrients as well as facilitating inter-species competition. Therefore, this study investigated the competition between soybean and Niger seed on yield and yield components, radiation efficiency, and yield advantage in the intercropping cultivation system. Material and MethodsA field experiment was conducted in two years (2018-19) at the Research Farm of Sari Agricultural Science and Natural Resources University, Iran (33º, 36ʹ N, 53º, 03ʹ E with 43 m altitude). The experiment was done based on a randomized complete block with four replications. The experimental treatment was 75% soybean + 25% Niger, 50% soybean + 50% Niger, 25% soybean+75% Niger based on the replacement method and soybean monoculture (100:0) and Niger monoculture (0:100). For example, a 25:75 combination included around three rows consisting of sowing a soybean and one row of Niger, along with vice versa in the 75:25 combinations. The 50:50 combinations also included planting two rows of each studied crops. The seed was sown directly on the 5th of May with a density of 28 plants per square meter. This study was investigated agronomic traits, radiation use efficiency, and the impact of competition on intercropping using Hill and Shimumoto models. Results and DiscussionBased on the achieved results, different planting ratios significantly affected plant height, dry weight, radiation use efficiency, yield, and yield components of both crops. The highest shoot heights of soybean and Niger with an average of 76.3 and 189.7 cm were related to planting ratio of 75:25, respectively. Also, the number of pods per plant of soybean and the number of capitule per plant of Niger in intercropping cultivation increased compared to monoculture. The reduction in the share of soybean and Niger sowing rows in different intercropping ratios increased the crop yield components. Also, the shoot’ dry weight of both crops increased in different planting ratios compared to the expected values. The highest percentage of dry shoot weight in soybean and Niger was related to 25:75 and 75:25 planting ratios, respectively. Besides, during different stages of growth, the radiation use efficiency of Niger in planting ratio was 50:50 and 25:75 higher than soybean. Also, the amount of radiation use efficiency in intercropping cultivation was more elevated than in monoculture. Due to the growing trend in its amount compared to the expected values, the effect of competition on radiation use efficiency during different growth stages was the type of mutual co-operation. According to the results, soybean (100:0) and Niger monoculture (0:100) had the highest and lowest grain yield with an average of 4965.7 and 462.4 kg. ha-1, respectively. Among the different intercropping, the combination 75:25 with an average of 4173.73 kg. ha-1 had the highest grain yield. Finally, the average land equivalent ratio in all different intercropping ratios was more than one, and the planting ratio of 50:50 had the highest average yield (LER = 1.28).ConclusionIncreasing resource utilization efficiency and establishing a mutual co-operation relationship is essential in improving the usefulness of Soybean and Niger intercropping cultivation compared to monoculture. Furthermore, the selection of Niger in intercropping systems can be beneficial due to their morphological features and facilitation of competition.